Degradation of remazol dyes-containing wastewater using integrated anaerobic-aerobic and aerobic Sequencing Batch Reactors (SBRs) - Khairil Anuar, Mohammad Pakri (Universiti Malaysia Perlis (UniMAP), 2013)
Access is limited to UniMAP community.